1991
DOI: 10.1093/jmedent/28.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of Carbon Dioxide Baits for Sampling Ornithodoros turicata (Acari: Argasidae) in Gopher Tortoise Burrows

Abstract: Field studies were conducted to assess the reliability of carbon dioxide baits in sampling Ornithodoros turicata Duges. Tick response to about 50 g of dry ice placed at various distances away from tick-infested burrows was monitored over a 2-h period. In addition, tick attraction to different flow rates of carbon dioxide was monitored. Tests were conducted over a 15-mo period, during which seasonal effects on O. turicata response to CO2 were assessed. The efficacy of the baits was evaluated at night and in day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Larval I. hirsti have only been recorded on passerines in South Australia (Kleindorfer et al 2006;Oorebeek and Kleindorfer 2008a). Field studies have shown that many tick species are attracted to a CO 2 source at a distance of 4 m (Wilson et al 1972;Koch 1987;Adeyeye and Butler 1991;Solberg et al 1992). However, many of these studies have been performed using mammalian ticks.…”
Section: Discussionmentioning
confidence: 99%
“…Larval I. hirsti have only been recorded on passerines in South Australia (Kleindorfer et al 2006;Oorebeek and Kleindorfer 2008a). Field studies have shown that many tick species are attracted to a CO 2 source at a distance of 4 m (Wilson et al 1972;Koch 1987;Adeyeye and Butler 1991;Solberg et al 1992). However, many of these studies have been performed using mammalian ticks.…”
Section: Discussionmentioning
confidence: 99%
“…There is the possibility that ticks attach only after a bat has fallen dead to the ground. However, it is well established that ticks are attracted to living animals by CO 2 [67]. Also, over the study period a minimum of two people were spending 1–2 hours every day for four months every year in the tick affected camps and never picked up one tick.…”
Section: Limitationsmentioning
confidence: 94%
“…In north-central Florida, most ticks inhabit the upper strata of burrows during the warm, humid months. In a later study, Adeyeye and Butler (1991) found that the efficacy of carbon dioxide baits as tick attractants was completely lost at night whenever the ambient temperature fell below 9°C. During the day, ticks were not attracted to carbon dioxide baits whenever the RH fell below 60%.…”
Section: Introductionmentioning
confidence: 95%
“…That O. turicata mated but failed to oviposit at 22°C/90% RH and 22°C/95% RH revealed the possibility of an adaptation which delays oviposition when the ambient conditions are not suitable for the survival of eggs or larvae. Adeyeye and Butler (1991) reported that O. turicata are not attracted to carbon dioxide and animal baits whenever the ambient temperature and RH fell below 10°C and 50%, respectively. The non-attraction to potential hosts below this temperature and humidity might be an indication of the threshold below which ticks would not mate.…”
Section: Influence Of the Temperature And Humidity On Mating And Ovipmentioning
confidence: 99%